2011
DOI: 10.1371/journal.pone.0022919
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role for the Fifth Component of Complement (C5) in Cardiac Physiology

Abstract: We have previously demonstrated that C5-deficient A/J and recombinant congenic BcA17 mice suffer from cardiac dysfunction when infected with C. albicans blastospores intravenously. During these studies we had observed that, even in the control un-infected state, BcA17 hearts displayed alterations in gene expression that have been associated with pathological cardiac hypertrophy in comparison to parental C5-sufficient C57Bl/6J (B6) mice. Of note was an increase in the expression of Nppb, a member of the fetal g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
1
10
0
2
Order By: Relevance
“…C5a 1 receptor has been shown to control osteoblast migration during fracture healing (Ignatius et al, 2011a), and efficient osteoclast differentiation requires local complement activation (Ignatius et al, 2011b). Normal heart function appears to depend on the C5a/C5a 1 receptor axis, with C5 deficiency and receptor knockout or blockade causing a "state of distress" (Mullick et al, 2011). C3a also has positive effects on food intake regulation, with the administration of C3a to the central nervous system leading to suppression of appetite (Ohinata et al, 2002(Ohinata et al, , 2007(Ohinata et al, , 2009Ohinata and Yoshikawa, 2008).…”
Section: B Functions Of the Complement Peptides Beyond Innate Immunitymentioning
confidence: 99%
“…C5a 1 receptor has been shown to control osteoblast migration during fracture healing (Ignatius et al, 2011a), and efficient osteoclast differentiation requires local complement activation (Ignatius et al, 2011b). Normal heart function appears to depend on the C5a/C5a 1 receptor axis, with C5 deficiency and receptor knockout or blockade causing a "state of distress" (Mullick et al, 2011). C3a also has positive effects on food intake regulation, with the administration of C3a to the central nervous system leading to suppression of appetite (Ohinata et al, 2002(Ohinata et al, , 2007(Ohinata et al, , 2009Ohinata and Yoshikawa, 2008).…”
Section: B Functions Of the Complement Peptides Beyond Innate Immunitymentioning
confidence: 99%
“…Zhang et al recently demonstrated complement activation during hypertension and that a C5a receptor signaling pathway on blood monocytes/macrophages played a pathological role in angiotensin II-induced cardiac inflammation and remodeling (Zhang et al, 2014). Conversely, C5a-receptor deficiency in a murine knock-out model has been associated with decreased resistance to cardiac stress, underscoring that complement might act as a double-edged sword also in the heart (Mullick et al, 2011). The mechanisms for in situ increased complement activation in heart failure are currently unknown, but myocardial levels of complement factor B are upregulated after myocardial infarction through toll-like receptor signaling and inflammatory cytokines (Singh et al, 2009;Singh et al, 2012).…”
Section: Pathogenic Role Of Complement In Heart Failure Developmentmentioning
confidence: 99%
“…It is generally thought that the C5aR-mediated classical PI3K signal is controlled by the ERK1/2 pathway. Moreover, neutrophil in fl ux is decreased following the injection of bacterial endotoxin into the peritoneal cavity in C5-de fi cient mice (Mullick et al 2011 ;Snyderman et al 1971 ) . It is believed that the neutrophil C5aR works as a pro-in fl ammatory receptor during the initiation phase of acute in fl ammation.…”
mentioning
confidence: 99%